Burial terminology: a guide for researchers - Sprague, Roderick (AltaMira Press, 2005)
Introduction -- Historical background -- The field guide -- Discussion of the classification -- Form of disposal -- Body preparation -- Individuality -- Articulation -- Position -- Deposition -- Orientation, alignment, and facing -- Grave goods or inclusions -- Disposal container -- Features -- Description of disposal area -- Demography -- Excavation -- Data recording.